1997
DOI: 10.1002/(sici)1097-4660(199712)70:4<400::aid-jctb797>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of maize, sunflower, grape and tobacco residues

Abstract: : Pyrolysis of four agricultural residues (maize, sunÑower, grape and tobacco) has been carried out in order to quantify their energy content. The main characteristics of the charcoals formed and the nature and quantity of gases produced have been determined. The process was studied batchwise by varying the reaction time (15È60 min) and temperature (400È700¡C). Reaction times higher than 30 min do not exert any inÑuence while increasing temperature yields high Ðxed carbon solids, low volatile content and sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 0 publications
5
26
0
2
Order By: Relevance
“…It should be noted that, while the volatile matter content was evaluated on the milled sample (particle size <212 mm) the pyrolysis experiments were carried out on pellets of a relatively large size. Other authors have found similar values for the volatile matter content in char obtained from the pyrolysis of biomass [9].…”
Section: Solid Fractionsupporting
confidence: 68%
See 1 more Smart Citation
“…It should be noted that, while the volatile matter content was evaluated on the milled sample (particle size <212 mm) the pyrolysis experiments were carried out on pellets of a relatively large size. Other authors have found similar values for the volatile matter content in char obtained from the pyrolysis of biomass [9].…”
Section: Solid Fractionsupporting
confidence: 68%
“…The pyrolysis of biomass is a very versatile process since conditions such as temperature, heating rate, residence time, etc. can be optimised to maximize the production of char, oil or gas depending on which product is required [7][8][9][10][11][12][13]. In conventional pyrolysis a high yield of hydrogen-rich gas is obtained working at high temperature and for a long residence time [14,15], whereas char production is increased by using low temperature and a low heating rate [16].…”
Section: Introductionmentioning
confidence: 99%
“…The solid biochar comprising carbon and ash remaining after pyrolysis can be a potential absorbent material for catalyst or fertilizer support [14][15][16]. Furthermore, due its low sulfur and phosphorus contents, as well as its structural and reactivity properties, biochar can be used in chemical, pharmaceutical and food industries [17].…”
Section: Introductionmentioning
confidence: 99%
“…The pyrolysis of grape residue has been investigated under different experimental conditions [11,12]. Apart from the limited bench scale, both of the studies were carried out only through packed bed reactor.…”
Section: Introductionmentioning
confidence: 99%